Training load, stress, recovery, mood, and motivation of athletes with spinal cord injury in wheelchair rugby during a competitive preseason - Eduardo Stieler; Varley Teoldo da Costa; Aline ângela Silva Cruz; Ingrid Ludimila Bastos Lôbo; Franco Noce; Andrea Maculano Esteves; Marco Tulio de Mello; Andressa Silva (Universidade Estadual Paulista (UNESP), 2022)
Abstract Aim: This study aims to characterize the stress, recovery, mood, and motivation together with the training load of athletes with cervical spinal cord injury (CSCI) during a period of resumption of wheelchair rugby (WCR) training. Additionally, it aims to compare the psychological and load training aspects during a competitive preseason and determine the correlations between training load, mood, stress, and recovery. Methods: We evaluated variables such as mood (Brazilian Mood Scale, BRAMS), stress and recovery (Recovery-Stress Questionnaire for Athletes, RESTQ-Sport 76) and training load (Subjective Perception of Effort - SPE) of eight high-performance athletes of wheelchair rugby with CSCIs at three different times (E1 = returning from vacation, E2 = half of the preseason, and E3 = after 2 months of training) for 2 months at a monthly interval. We also evaluated motivation (Sport Motivation Scale) at E1 and E3. Results: Results indicated few changes during the competitive preseason in terms of stress, recovery, and mood. However, the training load decreased toward the end of this period. Furthermore, we found that physical complaints positively correlated with depression when resuming training. In the middle of the competitive preseason period, we also noted positive correlations between conflict/pressure and fatigue and between fatigue and energy loss. At the end of this period, the SPE and arbitrary units correlated positively with conflict/pressure. Conclusion: We found few changes during the competitive preseason in terms of stress, recovery, and mood but not motivation, which did not change during this period. On the other hand, the training load decreased at the end of the competitive preseason. Furthermore, we observed correlations between training load and psychological aspects at different times.